2021
DOI: 10.21273/hortsci15895-21
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Soil and Glyphosate Residue as a Function of Cassava Weed Management by Cover Crops in the Amazon Ecosystem

Abstract: Cassava production in Amazonas state deserves to be highlighted due to its great historical, social, and economic importance. Weed competition severely constrains cassava production in Amazonas. The use of cover crops is safe and very efficient at eliminating weeds while keeping the soil covered. The objective of this study was to evaluate physical properties of soil and glyphosate residues in storage roots as a function of the weed management in cassava. The experiment was carried out in a randomized complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Also [ 86 ], investigated the availability of glyphosate and AMPA in a total of 243 samples of various fruits, and reported that all samples were within the maximum permissible limit. However [ 87 ], reported that glyphosate and its metabolite, AMPA, were not detected in cassava within the cover crops in the Amazon ecosystem even with five applications per year. While glyphosate levels in soybeans were reported to be 1.8 mgKg −1 for three times applications of glyphosate which is above the cRfD allowable dose, it was concluded that glyphosate and AMPA concentrations were higher when sprayings were done later in the growing season, close to time of blooming [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also [ 86 ], investigated the availability of glyphosate and AMPA in a total of 243 samples of various fruits, and reported that all samples were within the maximum permissible limit. However [ 87 ], reported that glyphosate and its metabolite, AMPA, were not detected in cassava within the cover crops in the Amazon ecosystem even with five applications per year. While glyphosate levels in soybeans were reported to be 1.8 mgKg −1 for three times applications of glyphosate which is above the cRfD allowable dose, it was concluded that glyphosate and AMPA concentrations were higher when sprayings were done later in the growing season, close to time of blooming [ 83 ].…”
Section: Resultsmentioning
confidence: 99%